Trust your heart - Alfonsi, Alice (New York : Hyperion Paperbacks for Children, 2007)
When Will's long-lost father suddenly appears, Will does not know whether to trust him or her mother, who is not pleased to see her father.
"Comic inserts inside!"--Cover.
008-012.
Keywords: Trust -- Juvenile fiction; Parent and child -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Witches -- Juvenile fiction; Magic -- Juvenile fiction; Comic books, strips, etc; Occult fiction